Native ethnic language in the system of integral identity of the personality (on the basis of the Kabardino-Circassian language) - Leorena A. Kharaeva; Larisa Kh. Dzasezheva (Кавказология, 2025)
Against the backdrop of global crises threatening the very existence of humanity, research on the phenomenon of identity as a mechanism for protecting the integrity of the individual and a psychological regulator of social life has gained prominence in the social sciences. Today, particular interest lies in the factors contributing to the formation and successful functioning of identity. One of the most critical questions in analyzing identity is understanding the decisive role of culture and verbal languages in its formation. This fundamental idea leads the authors to argue that the development of identity is rooted in one’s native language, along with the ethnocultural features it shapes. To confirm this conclusion, an analysis was conducted on the role of the Kabardian-Circassian language within the structure of identity, which, according to the authors, comprises the following components: cognitive, value-based, personal identity, and social solidarity. An empirical study of Adyghe students studying outside the Kabardino-Balkarian Republic revealed that educational migration heightens the significance of their native language as a symbol of cultural belonging. The language transforms into a tool of resistance against assimilation, aligning with Berry’s theory of "cultural tension." Even when a language loses its everyday functional role, it retains its function as an identity marker, as demonstrated by the example of Adyghe Etiquette (Khabze).